Strategi Komunikasi Pariwisata pada Pengembangan Promosi Desa Wisata Glebek Dalam Kabupaten Banyuasin Sumatera Selatan - Oktarina, Elly; Zinaida , Rahma Santhi (IAI Nasional Laa Roiba Bogor, 2024)
Glebek Dalam village Agrowisata is one of the tourist attractions that has very good potential to be developed, through good development. This study aims to explain the tourism communication strategy in developing the promotion of the Glebek Dalam tourism village in Banyuasin district, tourism village in Banyuasin district, south Sumatera. The study of swot analysis theory is the basis for this research. This research is a qualitative research with a descriptive approach that takes ecotourism agrotourism in Glebek Dalam village. Data collection in this research wa carried out through observation, documentation and interviews. The research results show that there are two tourism communications and tourism online communications tourism is social media in the form of Instagram and print media as well as websites that are used to convey information messages to the public. A communication strategy was formed in the Glebek Dalam village Agrotourism is two-way communication, due to cooperation between management groups tourism involing related agnecies and village communities in developing Agrotourism in Glebek Dalam village. Keywords: Glebek Dalam village Agrotourism, communication strategy, tourist.